Magnetic nanotherapy of animals with carcinosarcoma Walker-256 - Orel, V. E.; Shevchenko, A.D.; Rykhalskyi, O.Yu.; Romanov, A.V.; Burlaka, A.P.; Lukin, S.N.; Venger, E. F.; Sydoryk, E. P.; Schepotin, I.B. (Reports of the National Academy of Sciences of Ukraine, 2014)
Our experiments have shown that the antitumor activity of magnetic nanotherapy depends on the magnetic nanocomplex (MNC) parameters. MNC consisted of nanoparticles Fe3O4 and antitumor drug doxorubicin. Tumor-transplanted animals were subjected to the irradiation by permanent magnetic and electromagnetic fields. The highest antitumor activity and the survival rate of animals were observed after the treatment by MNC with the larger magnetic moment of saturation, and the large area square of the hysteresis loop and the lower coercivity. Intratumoral temperature does not exceed 38 ºC. The obtained results can be used to treat cancer patients.